Exploring the fibrinolytic potential of marine Actinoalloteichus caeruleus isolated from Bay of Bengal coast - Kothari Neeti Suresh; Subathra Devi. C (BMC Microbiology)
Abstract Background One of the main causes of several cardiovascular diseases that have an elevated mortality rate globally is intravascular thrombosis. The current fibrinolytic enzymes, are quite expensive and have a lot of side effects, thus it is necessary to develop alternate, economical techniques for the low-cost manufacture of these vital enzymes. Microbial fibrinolytic enzymes have the capacity to break up these clots and are relatively cheaper with minimal side effects and quick growth rate. Marine actinomycetota are the most prolific prokaryotes, which are capable of synthesizing novel secondary metabolites and are of industrial importance in pharmaceutical and various other industries. Thus, the objective of the research is to isolate, screen and characterize fibrinolytic protease producing actinomycetota from marine samples. Results In this study, 35 actinomycetota have been successfully isolated from marine water and sediment samples. Among them, 12 isolates were protease positive and on secondary screening 5 isolates showed fibrinolytic activity. Out of the 5 isolates, one potent isolate’s clot lysis activity was found out to be 93.12 ± 0.18% and its fibrinolytic potential was determined on fibrin agar plates. Based on the morphological, physiological, biochemical, and molecular analysis, the potent strain (NK60) was identified as Actinoalloteichus caeruleus. Conclusions In this present study, a rare actinomycetota has been isolated from the Bay of Bengal coast. This is the first study reporting the potent fibrinolytic activity of A. caeruleus, isolated from marine water. This clot-busting enzyme has significant pharmacological value in the management of coronary artery diseases. In the near future, A. caeruleus can serve as an explicit source for commercial production of fibrinolytic enzymes.